(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The article presents the analysis and design of MIMO monopoly Antenna along with split ring resonator to get frequency notch characteristic in the wide band. Frequency notch characteristics are achieved by keeping the split ring resonators on one side of the substrate and on the back of the substrate at deficient ground structure a complementary split Ring resonator with respect to microstrip feeding. Between 2.5-9.5GHz and 12.548-20GHz the dual notch band characteristics are acquired. The inspected conformal characteristics of the antenna hold eminent unceasing reflection coefficient characteristics at different angles in the overall band. Analyzed the unit cell of the SRR and also examined the antenna impedance and radiation characteristics of the model.